ANALISIS PENDAPATAN DAN TINGKAT KESEJAHTERAAN MASYARAKAT NELAYAN DANAU PULAU BESAR DAN DANAU BAWAH DI KECAMATAN DAYUN KABUPATEN SIAK PROPINSI RIAU - Hendrik, Hendrik (Jurnal Perikanan dan Kelautan, 2011)
This research was conducted at Dayun Sub District Siak Regency Riau onFebruary 2010. This research aimed to analyze the income and the distributionoutcome fisherman household Pulau Besar Lake and Bawah Lake also to describewalfare fisherman society. The method use was survey method. The respondentswere 36 fisherman and data was callected as primary and secondary data.The research results showed that the income of fisherman household whouse the boat engine around about Rp 1.500.000-3.000.000, with the incomeaverage Rp 2.305.055/month. Where as the income of fisherman household whouse the boat around about Rp 1.000.000-2.000.000, with the income average Rp1.582.833/month. The outcome of fisherman household who used the boat engineabout Rp 1.500.000-1.900.000, with the outcome average Rp 1.719.000/month.Where as the outcome of fisherman household who used the boat Rp 1.100.000-1.500.000, with the income average Rp 1.328.500/month.According to BPS criterion, there were six household respondent un walfareand according to Bappenas there is four house hold respondent that walfare stilllow/poor, and according to Regional Minimum Salary so all of respondents theyearn upper UMR Siak Regency (Rp 976.000/month)